The poisonous solicitor the true story of a 1920s murder mystery - Bates, Stephen 1958- (Icon Books Ltd, 2023)
In 1922, Major Herbert Armstrong, a Hay-on-Wye solicitor, was found guilty of, and executed for, poisoning his wife, Katharine, with arsenic. Armstrong's case has all the ingredients of a classic murder mystery, from a plot by Agatha Christie or Dorothy Sayers (indeed some aspects of his story appear in Sayers' Unnatural Death). It is a near-perfect whodunnit. One hundred years later, Agatha Award-shortlisted Stephen Bates examines and retells the story of the case, evoking the period and atmosphere of the early 1920s, a time of newspaper sensationalism, hypocrisy and sanctimonious morality